Տարոնի Իննակնյա վայրի պաշտամունքի ծագման խնդրի շուրջ - Գագիկ Մարտոյան (ՀՀ ԳԱԱ հրատ.)
Армянский средневековый летописец Ован Мамиконян в своем труде "История Тарона" рассказывает о том, как индийские князья Деметр и Гисиане, прибыв в Армению, устанавливают культ на горе Карке, в Тароне. В том же месте их потомки в дальнейшем воздвигают статуи идолов Деметр и Гисиане. Исследования показывают, что культ этих двух богов среди армян был связан с созвездиями Луны и Солнца—Девой и Геркулесом. The Armenian medieval annalist Hovhan Mamikonyan in his work < History of Taron > tells about Indian princes Demeter and Gesiane, who come to Armenia and establish a worship on the mountain Karke in Taron. Later on their descendants erect the statues of idols Demeter and Gesiane in the same place. The researches show that the worship of these two Gods among Armenians has been connected with the Moon and the Sun constellations Virgo and Hercules.
Keywords: History; Auxiliary Sciences of History; CC Archaeology; D History; G Geography; Anthropology; Recreation; GR Folklore